Orbital Pseudotumor: Uncommon Initial Presentation of IgG4-Related Disease - Teresa Carbone; Ricardo Azêdo Montes; Beatriz Andrade; Pedro Lanzieri; Luis Mocarzel (Case Reports in Rheumatology)
IgG4-related disease (IgG4-RD) encompasses a group of fibroinflammatory conditions recognized in recent times. The main clinical features include variable degrees of tissue fibrosis, tumorlike expansions, perivascular lymphocytic infiltration rich in IgG4-positive plasma cells, and elevated serum IgG4. A case has been reported of an elderly patient with an unexplained unilateral exophthalmia; biopsy was performed and revealed lymphocytic infiltration, suggesting IgG4-RD. High serum levels of IgG4, in association with a good response to steroid therapy and to the exclusion of other diagnoses, confirmed the hypothesis of orbital pseudotumor by IgG4-RD.